A new species of cirri-bearing eel of the genus Cirrhimuraena (Anguilliformes: Ophichthidae) from the coastal Bay of Bengal, India - Mohanty, Swarup Ranjan; Behera, Rajesh Kumar; Patro, Shesdev; Mohapatra, Anil (Zootaxa, 2023)
A new species of cirri-bearing ophichthidae eel Cirrhimuraena odishaensis sp. nov. is described here, on the basis of two specimens collected from the Palur canal and Talasari fish landing centre in Odisha, India. The distinguishing characters of Cirrhimuraena odishaensis sp. nov. that separate it from its congeners include the presence of a single row of mandibular teeth, origin of the dorsal fin directly above the midpoint of pectoral fin, vertebral counts (pre-dorsal 10, pre-anal 46–47, and total 160–162), and number of cirri (13) on the upper jaw. Morphologically Cirrhimuraena odishaensis shows close affinity with Cirrhimuraena yuanding and Cirrhimuraena orientalis. The new species differs from C. yuanding by origin of dorsal fin, number of intermaxillary and maxillary teeth, and length of head. The new species differs from C. orientalis with relatively higher vertebrae.